Long-term spectral responsivity stability of predictable quantum efficient detectors. (1st December 2022) - Porrovecchio, G; Linke, U; Smid, M; Gran, J; Ikonen, E; Werner, L
Abstract: The stability of induced junction silicon photodiodes used to construct the predictable quantum efficient detector (PQED) has been studied over a time period of a decade by measurements of its spectral responsivity against absolute cryogenic radiometers (CR) in two independent laboratories at CMI and PTB. PQEDs operated at room temperature show a long-term temporal stability within 150 ppm over a broad spectral range during a 10-year period, well within the range of the claimed measurement uncertainty values of the CRs. This long term stability fulfills one of the fundamental requirements to establish a new primary standard for the measurement of power of optical radiation.